'Daddy made a mistake and needed a time out': Incarcerated parents as moral educators. Issue 2 (3rd April 2023) - Kaiper-Marquez, Anna; Stickel, Tabitha; Prins, Esther
ABSTRACT: Although incarcerated individuals have committed potentially 'immoral' crimes, many are also parents, and need to foster their children's moral development. As such, incarcerated parents occupy a paradoxical position: they are labelled as morally deviant yet simultaneously expected to provide moral guidance for their children. This study explores the concurrent rifts and junctures between incarceration, parenting, and morality by revealing how incarcerated fathers at a Pennsylvania state correctional institution (SCI) used a family literacy program to offer moral instruction to their young children. Moreover, it examines the seeming paradox of how incarcerated parents viewed as morally culpable seek to shape their children's moral development while serving time for their own past actions. We find that although scholars and the public have historically perceived incarcerated individuals as lacking moral reasoning, there are multiple examples of incarcerated fathers acting as moral educators for their children.